Negaraku negara kita - Jamal Rizal Razali ([Kuantan], Pahang Darul Makmur : Penerbit Universiti Malaysia Pahang, 2014)
On nationalism, politics and government in Malaysia.
Bibliografi : muka surat 125-131.
Keywords: Nationalism -- Malaysia; Malaysia -- Politics and government